The triumph of the deviant: Social templates, mental reservation, and the ethics of coexistence in Sayaka Murata’s convenience store woman - Xiao, Shiwei; Seong, Dongkwon (Edelweiss Applied Science and Technology, 2025)
This article explores how the protagonist of Sayaka Murata’s Convenience Store Woman, Keiko Furukura, embodies a marginalized identity that critiques the normative social templates imposed by Japanese society. Adopting a qualitative literary analysis approach, the study applies the metaphor of the “mental reservation”—a symbolic space of psychological resistance theorized in relation to Sherman Alexie’s Ten Little Indians—to examine how Keiko creates internal distance from societal conformity. Situated in contemporary Tokyo, Keiko's mechanized labor and rejection of romantic and career norms manifest an alternative “ethics of belonging” based on mutual recognition and emotional detachment. The article argues that the novel’s postmodern narrative does not seek resolution through normalization but instead imagines an ethical community grounded in deviance, silence, and emotional otherness. These findings reveal how the narrative offers a blueprint for resisting dominant cultural scripts while preserving individual subjectivity. Ultimately, this study concludes that Convenience Store Woman reimagines the ethical architecture of community by celebrating the triumph of the deviant. The implications extend beyond literary criticism, offering new perspectives on cultural resistance, identity reconstruction, and ethical coexistence in contemporary Japanese society.